Identification of NAD-RNA species and ADPR-RNA decapping in Archaea - José Vicente Gomes-Filho; Ruth Breuer; Hector Gabriel Morales-Filloy; Nadiia Pozhydaieva; Andreas Borst; Nicole Paczia; Jörg Soppa; Katharina Höfer; Andres Jäschke; Lennart Randau (Nature Communications, 2023)
Abstract NAD is a coenzyme central to metabolism that also serves as a 5′-terminal cap for bacterial and eukaryotic transcripts. Thermal degradation of NAD can generate nicotinamide and ADP-ribose (ADPR). Here, we use LC-MS/MS and NAD captureSeq to detect and identify NAD-RNAs in the thermophilic model archaeon Sulfolobus acidocaldarius and in the halophilic mesophile Haloferax volcanii. None of the four Nudix proteins of S. acidocaldarius catalyze NAD-RNA decapping in vitro, but one of the proteins (Saci_NudT5) promotes ADPR-RNA decapping. NAD-RNAs are converted into ADPR-RNAs, which we detect in S. acidocaldarius total RNA. Deletion of the gene encoding the 5′−3′ exonuclease Saci-aCPSF2 leads to a 4.5-fold increase in NAD-RNA levels. We propose that the incorporation of NAD into RNA acts as a degradation marker for Saci-aCPSF2. In contrast, ADPR-RNA is processed by Saci_NudT5 into 5′-p-RNAs, providing another layer of regulation for RNA turnover in archaeal cells.